2017
DOI: 10.1590/1806-9282.63.11.971
|View full text |Cite
|
Sign up to set email alerts
|

Association between the RAGE (receptor for advanced glycation end-products) -374T/A gene polymorphism and diabetic retinopathy in T2DM

Abstract: This meta-analysis reveals that the A allele of RAGE -374T/A polymorphism probably increase DR risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“… 11 A notable association of mutant A allele with elevated risk of DR was also found in Caucasian and Asian populations. 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 A notable association of mutant A allele with elevated risk of DR was also found in Caucasian and Asian populations. 4 …”
Section: Discussionmentioning
confidence: 99%
“…11 A notable association of mutant A allele with elevated risk of DR was also found in Caucasian and Asian populations. 4 Table-II: Association analysis of genotype distribution of 374T/A polymorphism among DNR, NPDR and PDR Groups. In contrast to this, various studies carried out in Asians, Caucasians, Chinese and Malaysians revealed no meaningful association of diabetic retinopathy with rs1800624 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A state of sustained hyperglycemia can promote protein and lipid glycation in consequence producing AGE, which promote the alteration of the structure and function of other proteins; AGE has affinity for receptors known as receptor for advanced glycation end product (RAGE). The RAGEs are immunoglobulins that when activated promote the secretion of cytokines, which further stimulate the complications of diabetes by increasing vascular permeability and inflammatory processes [105, 106]. These effects will promote a hypoxic state in the microcapillaries of the retina leading to the beginning of the angiogenic process in the PDR [106].…”
Section: Pathophysiology Of Diabetic Retinopathymentioning
confidence: 99%
“…The RAGEs are immunoglobulins that when activated promote the secretion of cytokines, which further stimulate the complications of diabetes by increasing vascular permeability and inflammatory processes [105, 106]. These effects will promote a hypoxic state in the microcapillaries of the retina leading to the beginning of the angiogenic process in the PDR [106]. It has also been found that AGEs and RAGE are overexpressed in DR, which leads to think that genetic polymorphisms of RAGE are probably involved in the DR pathophysiology [107].…”
Section: Pathophysiology Of Diabetic Retinopathymentioning
confidence: 99%